Investigation of the Color, Fastness and Antimicrobial Properties of Wool Fabrics Dyed with the Natural Dye Extracted from the Cone of Chamaecyparis Lawsoniana. (3rd July 2015) - Kilinc, Mehmet; Canbolat, Seyda; Merdan, Nigar; Dayioglu, Habip; Akin, Filiz
Abstract: In this study, the wool fabric was mordanted with natural mordant agents extracted from the waste of three different plants. After the mordanting process, the samples were dyed with the natural dye extracted from the cone of Chamaecyparis Lawsoniana. Finally, the fastness properties, color strength (K/S) values and antimicrobial properties of samples were investigated in terms of the type of mordant.